Fulla’s and Barbie’s Images in Relation to Women’s Beauty and Cultural Difference - Anindya, Juwita (UI Scholars Hub, 2013)
Most people know Barbie, a doll that conveys some values about culture and about the concept of women’s beauty. However, Barbie only represents one specific culture, which is Western culture. Different with Western culture, Eastern culture needs a doll who can represent their values. Then, Fulla appears as the representative of Eastern beauty. Fulla conveys some values about Eastern culture and about the new concept of women’s beauty which are different from Barbie. Fulla’s appearance here is thought can emphasize the cultural differences among the society, but it can give another choice to shape people’s new thought about the beauty of Eastern culture. Using Said’s orientalism will help the writer to support the arguments about Eastern culture that can be an equal competitor to Western culture nowadays.